Determinat Factors Corellated with IVA Test Among Couple of Childbearing Age - Puji Wahyuni; Christin Hiyana Tungga Dewi; Ribkha Itha Idhayanti (Midwifery and Nursing Research, 2019)
Background: Visual Inspection with Acetic Acid (VIA) or Inspeksi Visual Asam asetat (IVA) in Indonesian is a visual test using an acidic solution of vinegar and iodine Lugol solution on the cervix and sees the color change after it is smeared. Advantages IVA Tests are easy, inexpensive, effective, results can be instantly known, and the way is very simple.Purpose: to determine the factors associated with the participation of IVA tests in couples of childbearing age. The benefits of the study may have an effect to support the participation of IVA tests in couples of childbearing age.Methods: Type of research used in this research Analitic. Cross-sectional design used. Univariate analysis to know the frequency distribution of each variable. Bivariate analysis using Spearman Rank test. The population of 303 EFA, Determining the sample with slovin to 75 respondents. The sampling technique uses the proportional stratified random sampling, and the way sampling by computerization.Results: Based on the results of research enough knowledge level of 56% (42 respondents). Attitudes that agree with the participation of the IVA test is 62.7% (47 respondents), husband support IVA test that is 54.7% (41 respondents), health support worker IVA test that is 64% (48 respondents), respondents get access to information 53.3% (40 respondents), respondents who are willing to follow the IVA test is 65.3% (49 respondents). In Spearman Rank test there is a relationship between knowledge level with IVA test participation, ρ (0.048). There is no relationship between attitude with IVA test participation, ρ (0,145). There is a relationship between the support of the husband with the participation of the IVA test, ρ (0.000). There is no correlation between the support of health personnel with the participation of the IVA test, ρ (0407).Conclusion: Based the results of the study is expected Midwives support and improve counseling about the IVA test, respondents can increase of knowledge about IVA test information and husband always support the wife.